The complexity of school leadership in Spain: between leadership and educational management - Sergio Cored-Bandrés; María Mairal-Llebot; Sandra Vazquez-Toledo; Cecilia Latorre-Cosculluela (Institute of Advanced Engineering and Science, 2026)
School leadership in Spain faces notable complexity arising from bureaucratization, limited autonomy, and the insufficient professionalization of the role. This study, grounded in perspectives from distributed, transformational and instructional leadership, analyses leadership teams’ perceptions regarding access to the position, training, the competencies required, and the satisfaction associated with these functions. To this end, a qualitative design was employed, based on semi-structured interviews conducted with 24 teachers holding leadership positions. The data were examined through categorical content analysis with the support of NVivo, ensuring both inter- and intra-rater reliability. The study offers an original contribution by providing updated empirical evidence on how structural and organizational conditions shape motivations, training relevance, and the relational competencies that underpin participatory leadership models. The thematic analysis identified several recurring themes: positive evaluations of initial training, diverse motivations for assuming the role (from vocation to compulsory appointment), the emphasis on communicative, collaborative and organizational competencies, and ambivalent professional satisfaction, combining fulfilment with administrative overload. In conclusion, the study underscores the need for more contextualized, practical, and sustainable policies and training programs that strengthen effective and humane pedagogical leadership, addressing the persistent gap between current training and real school demands.